2019
DOI: 10.1103/physrevfluids.4.013501
|View full text |Cite
|
Sign up to set email alerts
|

Torsional solutions of convection in rotating fluid spheres

Abstract: A numerical study of the nonlinear torsional solutions of convection in rotating, internally heated, self-gravitating fluid spheres is presented. Their dependence on the Rayleigh number has been found for two pairs of Ekman (E) and small Prandtl (Pr) numbers in the region of parameters where, according to Zhang et al. [J. Fluid Mech. 813, R2 (2017)], the linear stability of the conduction state predicts that they can be preferred at the onset of convection. The bifurcation to periodic torsional solutions is su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 32 publications
(50 reference statements)
1
17
0
Order By: Relevance
“…The magnetic field is split into toroidal, G, and poloidal, H, components, and treated numerically as the velocity field v(r, θ, t ) = ∇ × ( (r, θ, t )r) + ∇ × ∇ × ( (r, θ, t )r) in Ref. [36], where the physical and dynamical properties of v were studied. Then…”
Section: Equations and Numerical Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The magnetic field is split into toroidal, G, and poloidal, H, components, and treated numerically as the velocity field v(r, θ, t ) = ∇ × ( (r, θ, t )r) + ∇ × ∇ × ( (r, θ, t )r) in Ref. [36], where the physical and dynamical properties of v were studied. Then…”
Section: Equations and Numerical Methodsmentioning
confidence: 99%
“…Since stress-free boundary conditions are applied, the conservation of the z component of the angular momentum is achieved in the way explained in Sánchez Umbría and Net [36]. At r = 0 only regularity conditions are required.…”
Section: Equations and Numerical Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in this regime weakly energetic nonlinear flows (weak branch of [32]), which include nonaxisymmetric RWs (steadily drifting flows in the azimuthal direction), have not been found although they were predicted by the linear theory [39]. The situation is different in the case of low Pr and stress-free boundaries [40], because the first convective instability is axisymmetric, i.e periodic torsional oscillations develop at the onset. That study revealed a rich dynamical regime including bifurcations to quasiperiodic flows and solutions in which the amplitude is slowly increasing and rapidly decaying, repeatedly.…”
Section: Introductionmentioning
confidence: 91%
“…Recent examples include studies of turbulence (Budanur et al. 2017), convection (Sánchez Umbría & Net 2019) and droplet breakup (Gallino, Schneider & Gallaire 2018).…”
Section: Introductionmentioning
confidence: 99%